(untitled) (Albayan Scientific Journal, 2023)
The aim of the present study was to determine some of the positive effects that the aqueous extract of cinnamon plant (Scholars) and the pure insulin drug could have on female rats induced by the induced diabetes mellitus (wohydrate 150 kg / all voxan injection) by 5% kg / monox injection (50% wohydrate / monoxidine injection). ) Dissolved in the physiological solution in a volume (0.1ml) of body weight. This study was conducted on 30 mice from the white mice. They were divided into two groups. The first group represents a control group and comprises 10 categories Warren The second group includes 20 mice injected material Alaluxan then divided this group into two high schools, one Jrat plant extract Mayi cinnamon and other drug injected insulin. . The aqueous extract of the cinnamon plant was administered orally at a dose (200mg / kg) of body weight. The insulin drug was injected with a dose of 0.02 units / mg / kg of body weight. lower blood sugar level in categories Warren induced with diabetes Balaluxan was then d households dose half-lethal (LD50) test the toxicity of the extract of cinnamon using laboratory rats by an oral dosage bit reached 100, 200, 300 and 500 mg / kg of body weight, and the results showed a lack of any toxic effect of the extract of cinnamon water, as well as have been used which dose of itself to determine the effective dose of the extract in reducing the level of glucose in the blood of animals healthy, as it is observed that the amount of 300 dose mg / kg body weight of the animal was the most efficient, and after the end of the probation period 30 days from injury With oxan-induced diabetes and treatment with aqueous cinnamon extract, the animals were starved for 18 hrs. for the purpose of measuring the level of glucose in the blood serum, was observed decline in the level of serum glucose in a significant decrease after giving cinnamon extract to the treatment group compared with its positive control group infected and also outperformed the treatment group.